If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = -1 Reorder the terms: -2 + 3x = -1 Solving -2 + 3x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3x = -1 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = -1 + 2 3x = -1 + 2 Combine like terms: -1 + 2 = 1 3x = 1 Divide each side by '3'. x = 0.3333333333 Simplifying x = 0.3333333333
| 3x-2=-1 | | 3x-2=-1 | | 3x-2=-1 | | 3z-2=-1 | | 7x+8(11)=9 | | 2w+7x-15y+8w+7x+10y= | | 15-3+20=x-3 | | 216-2x=43x+16 | | (x+5)*2-(x-3)*2=x+1 | | 1-3=5 | | 10-(2z-9)=1-3z | | (2x-1)x^2=0 | | 14x-5=9x+17 | | 5-2(3-2x)=-1 | | [16.9+10]= | | 6(3x-5)-7=25 | | -18-2=x-7 | | (19+9)+(9)= | | 3(2x-5)=1-(2-4x) | | 5x+3=8x+10 | | -12+x-3=15-18+9 | | 3x+(2x+30)=180 | | 149-6x=30x+21 | | 9x-6w-4y+3w+3x+9y= | | -65+25+12= | | (x/2)+3=4x-(2/3) | | 54-2x=-8 | | 4y+50=5y+42 | | -(-21+6)=(21)+(6) | | 5-5(-9a-6)=2-6(6+4a) | | 27-11x=14x-18 | | (1+i)(1+i)(1+i)= |